Exploring Organizational Growth Potential Through SWOT and Porter’s Five Forces: A Strategic Approach - Popy Novita Pasaribu; Shanty Iyssandra; Rosseh, Akbar (Al-Qalam Institue, 2025)
This study aims to analyze the potential and strategic development of an Islamic banking organization using the SWOT analysis and Porter’s Five Forces framework. Amid increasing competition in the Islamic banking sector, effective strategies are essential to expand market share, enhance service performance, and maintain competitiveness. The research was conducted at the organization’s head office using a descriptive qualitative approach, complemented by quantitative methods through IFE (Internal Factor Evaluation) and EFE (External Factor Evaluation) scoring, along with strategy mapping in the SWOT matrix. The results show an IFE score of 0.51 and an EFE score of 0.91, placing the organization in Quadrant I (Aggressive Strategy), indicating strong internal capabilities and effective utilization of external opportunities. Key strengths include a strong local reputation, competent human resources, and diverse Sharia-compliant savings products. However, weaknesses were found in limited digital innovation and uneven marketing reach. External opportunities include rising public awareness of Islamic finance, digital advancements, and supportive government regulations. Porter’s analysis revealed high bargaining power of buyers and suppliers, strong threat of substitutes, and intense competition in regions like Bogor. Recommended strategies include digital service enhancement, partnerships with educational and religious institutions, and public literacy campaigns on Islamic finance to drive sustainable growth.